Study in Surgical Procedure in Obstruct Metastatic Colon Cancer - แสงวันลอย ประเวทย์ (Journal of Health Science of Thailand, 2021)
Metastatic colon cancer has multiple surgical methods. No studies have yet been made to clear guidelines on surgery. Surgery by using colostomy causes severe suffering for patients. This research was created to find out whether or not colon cancer has spread. Primary resection with anastomosis has many complications whether or not the loop is colostomy or Hartmann’s procedure. Colon cancer patients have been obstructed in Nan Hospital since the year 2000. 2010 to 2019, 79 patients with metastatic colorectal cancer, obstructing 27 patients. No complications were found in the primary resection with anastomosis such as Respiratory event, Cardiovascular event or Leakage in primary resection patients. In addition, the duration of surgery to receive chemotherapy in Primary resection with anastomosis is not different from the lifting of Hartmann’s procedure (p = 0.253), Loop colostomy (p = 0.161). However, the survival rate in patients. Metastatic colon cancer that has been surgically removed Unlike the survival rate in patients with metastatic colorectal cancer that is only looped and not surgically removed (p = 0.401). The authors suggest that patients with metastatic colon cancerbe primary resection with anastomosis if there are no contraindications.